Long‐term real‐life safety profile and effectiveness of fumaric acid esters in psoriasis patients: a single‐centre, retrospective, observational study. (18th May 2018) - Dickel, H.; Bruckner, T.; Altmeyer, P.
Abstract: Background: Fumaric acid esters (FAEs) are an established systemic treatment for moderate‐to‐severe psoriasis. However, the long‐term clinical safety and effectiveness of continuous FAE monotherapy and combination therapy have not been established. Objective: To examine the long‐term safety and effectiveness of FAEs as monotherapy and in combination with phototherapy or methotrexate in patients with psoriasis treated at a single centre in Germany. Methods: This monocentric, retrospective observational study, with a follow‐up period of up to 32.5 years, included 859 patients: 626 received FAE monotherapy, 123 received FAEs with concomitant phototherapy and 110 received FAEs with methotrexate. Results: Approximately half of patients (49.0%) reported adverse events (566 total events), most of which involved the gastrointestinal tract. Serious adverse events were reported in 2.3% of patients, but none were deemed to have a causal relationship with any of the treatment regimens. Adverse events leading to treatment discontinuation were observed in 12.9% of patients. A median duration of 1 year was observed in all three treatment subcohorts ( P = 0.70) from initiation of FAE treatment to a 50% response rate, where response was defined as achieving a cumulative static Physician's Global Assessment (PGA) score of 'light' and at least a 2‐point reduction in baseline PGA. A 50% response rate for the cumulative Psoriasis Area and Severity Index 75 was achieved in the FAE monotherapy subcohort after a median of 3 years of treatment, in the FAEs + phototherapy subcohort after 6.7 years and in the FAEs + methotrexate subcohort after 8.1 years ( P = 0.001). Conclusion: According to our data, FAEs as monotherapy or in combination with phototherapy or methotrexate are safe and beneficial for long‐term clinical use. However, multicentre, randomized controlled trials are required to establish the clinical value of monotherapy versus combination therapy and the optimal treatment duration.